Rancang Bangun Aplikasi E-Catalogue Buku Perpustakaan Berbasis Website di Yayasan Pusat Perguruan Fatahillah - Dede Handayani; Ahmad Haical Ramadhan; Muhammad Fauzan; Muhamad Rafly Rafsanzany (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research aims to design and build a website-based library book e-catalog application at the Fatahillah College Center Foundation. This application is designed to overcome the limitations of the manual system currently used by libraries, increase the efficiency of book information management, and make information access easier for users. The research methods used include descriptive methods, observation, interviews, and system development using the Waterfall model. The research results show that the e-catalog application can manage book, member, and loan transaction data effectively. It is hoped that implementing this application can support literacy activities and increase library operational efficiency.